Comparison of Three-Dimensional Visualization Techniques for Depicting the Scala Vestibuli and Scala Tympani of the Cochlea by Using High-Resolution MR Imaging - Hans, Paul; Grant, Andrew J.; Laitt, Roger D.; Ramsden, Richard T.; Kassner, Andrea; Jackson, Alan (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Cochlear implantation requires introduction of a stimulating electrode array into the scala vestibuli or scala tympani. Although these structures can be separately identified on many high-resolution scans, it is often difficult to ascertain whether these channels are patent throughout their length. The aim of this study was to determine whether an optimized combination of an imaging protocol and a visualization technique allows routine 3D rendering of the scala vestibuli and scala tympani.METHODS: A submillimeter T2 fast spin-echo imaging sequence was designed to optimize the performance of 3D visualization methods. The spatial resolution was determined experimentally using primary images and 3D surface and volume renderings from eight healthy subjects. These data were used to develop the imaging sequence and to compare the quality and signal-to-noise dependency of four data visualization algorithms: maximum intensity projection, ray casting with transparent voxels, ray casting with opaque voxels, and isosurface rendering. The ability of these methods to produce 3D renderings of the scala tympani and scala vestibuli was also examined. The imaging technique was used in five patients with sensorineural deafness.RESULTS: Visualization techniques produced optimal results in combination with an isotropic volume imaging sequence. Clinicians preferred the isosurface-rendered images to other 3D visualizations. Both isosurface and ray casting displayed the scala vestibuli and scala tympani throughout their length. Abnormalities were shown in three patients, and in one of these, a focal occlusion of the scala tympani was confirmed at surgery.CONCLUSION: Three-dimensional images of the scala vestibuli and scala tympani can be routinely produced. The combination of an MR sequence optimized for use with isosurface rendering or ray-casting algorithms can produce 3D images with greater spatial resolution and anatomic detail than has been possible previously.